PENGARUH KARBURASI ARANG TERHADAP KEMAMPUKARESAN BAJA ST 42 DENGAN METODE JOMINY - Yusuf, Yusuf; Ruchiyat, Asep; Helanianto, Helanianto (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2022)
Hardenability is the ability of a material to harden to a certain depth utilizing heat treatment to form martensite upon cooling to achieve a certain hardness. The hardness of a metal, especially steel, can be modified without adding alloying elements and is done by heat treatment. Steel's hardenability value is strongly influenced by the carbon content (carburizing) in the steel structure. Increasing the hardness of a material can be done by adding carbon to the object's surface during heat treatment. The Rockwell Hardness Test method measures the surface of the hardness. The test results on the specimens showed that the carburizing process of each specimen increased the hardness of the surface of the specimen. The distribution of hardenability values ​​is close to a linear line, namely the heat treatment temperature 900oC.